Janet Burnett Grossman. The Athenian Agora Vol. XXXV: Funerary Sculpture. - Spivey, Nigel (Journal of Greek Archaeology, 2017)
The Agora of Athens was never a cemetery. That observation, elementary enough, warns the reader of this corpus not to expect an array of integral and wonderful monuments. Such funerary sculpture as recovered during the Agora excavations (since 1931) is necessarily dislocated – most probably, from the nearby Kerameikos, though of the inscribed families only one gives Kerameis as deme; and usually dismembered, having been used (and often re-used) as landfill or construction material down the ages. The effect of the ensemble, numbering 389 catalogue entries, is poignant: so many shattered and battered pieces of tombstones once intended for perpetuity.